Physical modeling of drums by transfer function methods - Trautmann, Lutz; Petrausch, Stefan; Rabenstein, Rudolf (2001 IEEE Interntional Conference on Acoustics, Speech, and Signal Processing, 2001)
Multidimensional (MD) physical systems are usually given in terms of partial differential equations (PDEs). Similar to one-dimensional systems, they can also be described by transfer function models (TFMs). In addition to including initial and boundary conditions as well as excitation functions exactly, the TFM can also be discretized in a simple way. This leads to suitable implementations for digital signal processors. Therefore it is possible to implement physics based digital sound synthesis algorithms derived from TFMs in real-time. This paper extends the recently presented solution for vibrating strings with one spatial dimension to two-dimensional drum models.